Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Kasus pada SD Negeri 038 Kiaracondong, Bandung). - Suryawan, Qanita Azahra; Deri Apriadi (Pusat Riset dan Inovasi Nasional, 2025)
The research here aims to find out how the influence of training variables (X1) and work discipline (X2) on employee performance (Y) at SD Negeri 038 Kiaracondong, Bandung using a quantitative approach. A total of 30 respondents were used as samples for this study, where the data collection process was carried out by distributing questionnaires to the population at SD Negeri 038 Kiaracondong. Data were analyzed using the SPSS version 25 analysis program. The test results showed that (1) Training variables have an impact on employee performance, the t-count value was 1.732> t-table 1.697 and Sig 0.001 <0.05. The results of the multiple linear regression analysis showed results on the increase that an increase in training of 0.181, then it will increase employee performance by 0.181 constantly. (2) The work discipline variable is proven to have a positive impact on employee performance variables, with a t-count value of 2.106 > t-table 1.697 and Sig 0.004 < 0.05. The results of multiple linear regression analysis reveal that an increase in work discipline of 0.321 will increase employee performance by 0.321 constantly. (3) Together, training and work discipline have a significant impact on employee performance, with an F-count value of 2.245 < F-table 4.20 and obtaining a Sig value of 0.000 < 0.05. (4) The results of the R² determination coefficient test show that X1 and X2 have an effect of 14.3% on Y.